Startup Asia : top strategies for cashing in on the Asia's innovation boom - Fannin, Rebecca A. (Singapore. : John Wiley & Sons (Asia) Pte. Ltd, 2012)
Showing how entrepreneurs and investors can start up in Asia and go global, the book provides a first-hand, on-the-ground tour of the new technology centers that are gaining momentum all over Asia. Interviews with the most successful venture capitalists and entrepreneurs reveal their winning strategies and show how a new generation of entrepreneurs in China and India are no longer looking to the West for their cues - but are instead crafting their own local business models and success strategies.
Includes bibliographical references (P. 219-227) and index.
Keywords: Entrepreneurship; Technological innovations -- Asia